The Challenge of Decentralization Policy for Television Broadcasting in Indonesia - Rahayu Rahayu (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2023)
This study aims to explain the challenges in the decentralization of television broadcasting in Indonesia, specifically, the role of political transformation over the last 20 years. Three provinces, i.e., Bali, South Sulawesi, and Daerah Istimewa Yogyakarta, were selected to represent various broadcasting operation characteristics in Indonesian provinces. Focusing on private television broadcasting, the case study examines the challenge of broadcasting decentralization policies in Indonesia. Data were collected via structured interviews involving 37 informants with a good understanding of local television broadcasting. The interviews were conducted in March, April, and July 2017. Meanwhile, secondary data in the form of relevant documents were analyzed using a desk study. Data were collected in two stages: May-September 2018 and November 2020-March 2021. These steps follow the current policy development on broadcasting decentralization. The findings indicate that decentralization faces challenges and that the policy has been tainted by media conglomerates’ economic interests and the central government’s recentralization politics. The economic interests were apparent in the fabrication of capital ownership and the centralization of business management and broadcast program production. The recentralization interests were noticeable through the operation license mechanism in the regions. In sum, Indonesia’s decentralization policy faces perpetual challenges from the surge of capitalization and the centralization of governance.